2002
DOI: 10.1128/jcm.40.5.1821-1823.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid PCR-Based Identification of Methicillin-Resistant Staphylococcus aureus from Screening Swabs

Abstract: A PCR identification of methicillin-resistant Staphylococcus aureus (MRSA), obviating the need for subculture on agar media, was investigated. The combination of MRSA detection by mecA femB PCR with prior enrichment in selective broth was tested for 439 swabs. PCR identified 36 MRSA-positive samples, in concordance with conventional methods.Accurate and rapid identification of methicillin-resistant Staphylococcus aureus (MRSA) in clinical specimens is essential for timely decisions on isolation procedures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
103
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(106 citation statements)
references
References 18 publications
1
103
0
2
Order By: Relevance
“…PCR primers specific for mecA gene (mecA1: GTAGAAAT-GACTGAACGTCCGATAA and mecA2: CCAATTCCACATT-GTTTCGGTCTAA) were selected from Jonas et al (20) and synthesized by Tib-Molbiol (Berlin, Germany). The PCR mixture containing; 10X PCR buffer, taq DNA polymerase (0.5 U/μl) (HT Biotechnology, Cambridge, United Kingdom), each primer (1.6 μM), MgCl2 (1.2 μM) and each dNTP (0.64 μM).…”
Section: Pcrmentioning
confidence: 99%
“…PCR primers specific for mecA gene (mecA1: GTAGAAAT-GACTGAACGTCCGATAA and mecA2: CCAATTCCACATT-GTTTCGGTCTAA) were selected from Jonas et al (20) and synthesized by Tib-Molbiol (Berlin, Germany). The PCR mixture containing; 10X PCR buffer, taq DNA polymerase (0.5 U/μl) (HT Biotechnology, Cambridge, United Kingdom), each primer (1.6 μM), MgCl2 (1.2 μM) and each dNTP (0.64 μM).…”
Section: Pcrmentioning
confidence: 99%
“…Biochemical testing showed that all isolates were catalase-positive, while 10 were also coagulase-positive. DNA from each colony was isolated and used in a multiplex PCR analysis ( Figure 1a) that targeted the 16S rRNA gene of Staphylococcus spp (Mason et al, 2001), femB (Jonas et al, 2002) and mecA (Jonas et al, 2002). The targeted femB sequence is S. aureus-specific and encodes a protein crucial for peptidoglycan crosslinking, while mecA has been established as a standard marker for confirming methicillin resistance in staphylococci (Clinical and Laboratory Standards Institute, 2006).…”
mentioning
confidence: 99%
“…A control, 'field blank' swab that was briefly exposed to the air in each computer facility was also collected. Swabs were incubated (48 h at 351C, with shaking) in tryptic soy broth (TSB) supplemented with oxacillin (2 mg l À1 ) (Jonas et al, 2002). Oxacillin has replaced methicillin as the current agent of choice for selecting bacteria that are resistant to penicillinase-stable penicillins.…”
mentioning
confidence: 99%
“…Multiplex PCR (agarose gel) detecting femB and mecA 100 100 3 [56,57] Real-time PCR detecting mecA 100 100 2 [58] High-throughput real-time PCR detecting mecA and nuc 100 100 2.5 [59] Real-time PCR detecting mecA and SA442 100 100 4 [60] Isothermal signal amplification (CytAMP) detecting coa and mecA 83 93 3.5 [61] Real-time PCR detecting nuc and mecA 93 90 2.5 [62] Direct from clinical specimen (swabs)…”
Section: Enrichmentmentioning
confidence: 99%